2019
DOI: 10.1007/s12298-019-00674-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of melatonin mitigates the adverse effects of drought stress on morpho-physiological traits and secondary metabolites in Moldavian balm (Dracocephalum moldavica)

Abstract: Melatonin has emerged as an important signaling molecule that regulates plant responses to environmental stresses. In this research, melatonin was used to alleviate the adverse effects of oxidative stress induced by water deficit in Moldavian balm (Dracocephalum moldavica) plants and morpho-physiological traits were investigated. This experiment was conducted as a factorial arrangement based on completely randomized design with four replications. Treatments included foliar melatonin application at four levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…These results indicated that melatonin delayed aging of kiwifruit leaves by activating the antioxidant capacity and enhancing flavonoid biosynthesis. In another studies, Bahcesular et al (2020) on basil ( O. basilicum L.), and Naghizadeh et al (2019) on moldavian balm ( D. moldavica L.) observed that foliar application of 100 μM melatonin increased secondary metabolites synthesis in plant under moderate and severe drought stress probably through regulation of secondary metabolism and the enzymes activity of PAL and polyphenol oxidase. The exogenous application of melatonin can improve plant antioxidant ability by enhancing antioxidant enzyme activities and alleviating leaf senescence by improving flavonoid production ( Yin et al, 2013 ; Ben Abdallah et al, 2016 ; Liang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…These results indicated that melatonin delayed aging of kiwifruit leaves by activating the antioxidant capacity and enhancing flavonoid biosynthesis. In another studies, Bahcesular et al (2020) on basil ( O. basilicum L.), and Naghizadeh et al (2019) on moldavian balm ( D. moldavica L.) observed that foliar application of 100 μM melatonin increased secondary metabolites synthesis in plant under moderate and severe drought stress probably through regulation of secondary metabolism and the enzymes activity of PAL and polyphenol oxidase. The exogenous application of melatonin can improve plant antioxidant ability by enhancing antioxidant enzyme activities and alleviating leaf senescence by improving flavonoid production ( Yin et al, 2013 ; Ben Abdallah et al, 2016 ; Liang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…Under drought stress, the demand for water increases, which leads to the recycling of scarce resources to reproductive sink tissues (Naghizadeh et al, 2019;. Melatonin application in Hordeum vulgare postpones induced senescence and delays the loss of chlorophyll (Li et al, 2016).…”
Section: Senescencementioning
confidence: 99%
“…The drought response and avoidance mechanism includes the adjustment of source/sink allocation, increase in root growth, stunted growth, and shedding/senescence of older leaves (Prasad et al, 2008). Under drought stress, the demand for water increases, which leads to the recycling of scarce resources to reproductive sink tissues (Naghizadeh et al, 2019; Sadak et al, 2020). Melatonin application in Hordeum vulgare postpones induced senescence and delays the loss of chlorophyll (Li et al, 2016).…”
Section: Melatonin‐mediated Regulation Of Plant Development Under Drought Stressmentioning
confidence: 99%
“…Exogenous application of melatonin contributes to the reduction of ROS accumulation and membrane damage, as evidenced by the decrease in H2O2, electrolyte leakage, and MDA content. Additionally, melatonin has been shown to reduce electrolyte leakage and MDA content in Cucumis sativus L. and Moldavian balm under moderate and severe drought stress (Zhang et al, 2013;Naghizadeh et al, 2019). Melatonin also acts as a powerful scavenger of ROS in plants (Arnao and Hernández-Ruiz, 2015).…”
Section: Results Results Resultsmentioning
confidence: 99%